Astrocyte reactivity and astrogliosis after spinal cord injury. (January 2018) - Okada, Seiji; Hara, Masamitsu; Kobayakawa, Kazu; Matsumoto, Yoshihiro; Nakashima, Yasuharu
Highlights: Glial scars form through the reactive response of astrocytes after CNS injury. Glial scars serve as a major barrier to regenerating axons and impair the functional recovery in SCI. Reactive astrocytes are beneficial to the wound healing and tissue remodeling processes in the subacute phase of SCI. The process of reactive gliosis is regulated by environmental factors, including type 1 collagen. Abstract: After traumatic injuries of the central nervous system (CNS), including spinal cord injury (SCI), astrocytes surrounding the lesion become reactive and typically undergo hypertrophy and process extension. These reactive astrocytes migrate centripetally to the lesion epicenter and aid in the tissue repair process, however, they eventually become scar-forming astrocytes and form a glial scar which produces axonal growth inhibitors and prevents axonal regeneration. This sequential phenotypic change has long been considered to be unidirectional and irreversible; thus glial scarring is one of the main causes of the limited regenerative capability of the CNS. We recently demonstrated that the process of glial scar formation is regulated by environmental cues, such as fibrotic extracellular matrix material. In this review, we discuss the role and mechanism underlying glial scar formation after SCI as well as plasticity of astrogliosis, which helps to foster axonal regeneration and functional recovery after CNS injury.